The Role of Islamic Banks in Economic Development - Hassan, Guled Ali (2015)
Islamic banking was established to contribute more to social and economic development. It offers several advantages over conventional banks which include efficiency, stability,reduced moral hazard and being more responsive to society needs. The current study focused on Islamic banks or other conventional banks that provide Islamic financial products in Kenya. Out of the 43 banks in Kenya, only 13 offered Islamic banking products. The purpose of this research was to establish the role of Islamic banking in economic development in Kenya. The study applied both quantitative and qualitative methods. The quantitative methods involved using questionnaires to do a numerical analysis and generalizing it to depict the role of Islamic banking on economic development. The qualitative methods involved using open-ended questions in the questionnaire and interviews with senior bank employees heading Islamic banking units. Fifty two questionnaires (four in each bank) and thirteen interviews were arranged. Data collection was conducted in the month of March and April 2015. The study findings revealed that clients were motivated to join Islamic banking in Kenya due to their Islamic investment principles such as prohibition of interest, profit sharing and dividends on savings. Islamic banking products on offer included ijarah, mudaraba, rab-al-maal,musharaka, sukuk, takaful, tawarruq, wadia, wakalah, istisna and bai salam. However,most banks over relied on mudarabah. Results indicated that the Islamic banking products provided by the surveyed banks were fully shariah compliant except for Al-Qard Al-Hassan where compliance was poor. The results further indicated that profit sharing was the most significant factor in Islamic banking that contributed to economic development. Other factors contributing significantly were demanding that any finance provided should be used for legitimate trade or investment, prohibition of riba,prohibition of excessive uncertainty and prohibition of harmful activities. Moreover,results indicated that Islamic banking has contributed to creation of employment,development in the construction and real estate development sector, development of the manufacturing sector, development in SMEs, lowering inflation and improving in liquidity in the economy.Islamic banking is most active in finance and banking,insurance, housing, manufacturing and tourism. Those sectors where Islamic banking was least active were fisheries and agriculture. Recommendations are made to Islamic banks to introduce long-term saving funds, allowing them to increase their deposits, and enabling them to carry out long-term investments that effectively contribute in achieving economic development. Further Islamic banks ought to give attention to long-term investment financing, and not merely focus on short-term financing. Additionally,Islamic banks should increase their financing to agricultural and industrial sectors. Recommendations to policy making authorities include pushing Islamic banks to initiate vital changes in investment and oblige them to direct their investments in a way that serves the priorities of economic development, reviewing banking legislations that govern Islamic banks and encouraging Islamic banks to develop their available banking products in terms of geographic availability and quality, in a way that helps to broaden their reach, accumulate savings and direct them towards financing investment activities that contribute towards economic growth.